IMPLEMENTASI PROGRAM JAKPRENEUR PADA UMKM BINAAN DINAS PERINDUSTRIAN, PERDAGANGAN, KOPERASI, USAHA KECIL DAN MENENGAH DI KECAMATAN TANJUNG PRIOK - Azkia Himayatu Dini (Puslatbang KHAN, 2022)
ABSTRACT The development of UMKM is an important thing to do, considering its contribution to GDP and its potential number. Especially the UMKM assisted by the PPKUKM Service in Tanjung Priok District which have more potential numbers than other sub-districts in North Jakarta City. The implementation of the Jakpreneur Program is one of the efforts to develop UMKM and reduce various increases in entrepreneurship opportunities. This research was conducted with the aim of knowing the implementation of the Jakpreneur Program Implementation at UMKM Assisted by the PPKUKM Service in Tanjung Priok District. Keywords: Implementation, Jakpreneur, UMKM, Tanjung Priok District